Risk perception matters: why women's passion may not lead to a business start-up. Issue 1 (9th March 2015) - Dalborg, Cecilia; von Friedrichs, Yvonne; Wincent, Joakim
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to explore whether nascent women entrepreneurs perceive more risks than men, and to determine how higher risk perceptions might limit start-up decisions by mediating the potential influence of passion and self-efficacy. Design/methodology/approach – This study surveyed 103 participants in Sweden – both women and men – who, in the period 2008 through 2011, intended to start a business. ANOVA tests and binominal logistic regression models were conducted to test hypothesized framework. Findings – The authors found that nascent women entrepreneurs perceive more risk than nascent male entrepreneurs, that risk perceptions influence start-up decisions and that risk preferences partial out the otherwise identified influence of passion on start-up decisions. Research limitations/implications – The authors reveal a consequence of gender socialization and how it impacts the start-up decisions of nascent women entrepreneurs. Support systems should consider developing activities that change the public's perception of who is an entrepreneur and seek ways to balance risk perceptions between men and women. Originality/value – The authors argue here that risk perceptions play a prominent role in start-up decisions. Specifically, they consider that nascent women entrepreneurs perceive more risks than men, and that their view of risk partials out any potential influence of their perceived passion and self-efficacy on their start-up decision.